Thirty Years of Territorial Restructuring in Greece (1981-2010) - Leontitsis, Vasilis (Ελληνική Επιθεώρηση Πολιτικής Επιστήμης, 2017)
This article examines the decentralisation process that took place in Greece from 1981 until 2010. Although Greece remains a highly centralised state, considerable decentralization reforms were undertaken during this period. Those reforms affected all subnational levels of government. Nevertheless, despite the considerable changes, the fundamentals of the polity have remained relatively untouched. The paper examines the causal factors of decentralisation reforms throughout this period alongside the obstructing factors that resisted them, thus contributing towards the relative inertia of the polity structures. The main argument put forward is that it was mainly domestic factors that shaped the decentralization process in the country. Party politics, the démocratisation discourse and, later on, managerial concerns influenced the reform process greatly. Additionally, structural characteristics of the Greek socio-political system, such as veto points at the local and national levels, obtruded change, while the role of certain individual actors who acted as policy entrepreneurs and pushed the reforms up the political agenda should not be underestimated. Europeanisation and other international factors were of secondary importance in the whole process. Nevertheless, one should not overlook them altogether, since their interrelation with the aforementioned domestic factors produced considerable consequences.